Structural and spectroscopic characterization of two new blue luminescent pyridylbenzimidazole zinc(II) complexes. Issue 6 (17th May 2016) - DeStefano, Matthew R.; Geiger, David K.
Abstract : The structures of two zinc(II) complexes of 5, 6‐dimethyl‐2‐(pyridin‐2‐yl)‐1‐[(pyridin‐2‐yl)methyl]‐1 H ‐benzimidazole were determined. The absorption and emission data of the complexes and the free ligand are reported. The spectra are examined in the context of a frontier orbital analysis based on DFT calculations of the benzimidazole ligand and the zinc(II) complexes. Abstract : Luminescent metal complexes are used in photooptical devices. Zinc(II) complexes are of interest because of the ability to tune their color, their high thermal stability and their favorable carrier transport character. In particular, some zinc(II) complexes with aryl diimine and/or heterocyclic ligands have been shown to emit brightly in the blue region of the spectrum. Zinc(II) complexes bearing derivatized imidazoles have been explored for possible optoelectronic applications. The structures of two zinc(II) complexes of 5, 6‐dimethyl‐2‐(pyridin‐2‐yl)‐1‐[(pyridin‐2‐yl)methyl]‐1 H ‐benzimidazole ( L ), namely dichlorido(dimethylformamide‐κ O ){5, 6‐dimethyl‐2‐(pyridin‐2‐yl‐κ N )‐1‐[(pyridin‐2‐yl)methyl]‐1 H ‐benzimidazole‐κ N 3 }zinc(II) dimethylformamide monosolvate, [ZnCl2 (C20 H18 N4 )(C3 H7 NO)]·C3 H7 NO, (I), and bis(acetato‐κ 2 O, O ′){5, 6‐dimethyl‐2‐(pyridin‐2‐yl‐κ N )‐1‐[(pyridin‐2‐yl)methyl]‐1 H ‐benzimidazole‐κ N 3 }zinc(II) ethanol monosolvate, [Zn(C2 H3 O2 )2 (C20 H18 N4 )]·C2 H5 OH, (II), are reported. Complex (I) crystallized as a dimethylformamide solvate and exhibits a distorted trigonal bipyramidal coordination geometry. The coordination sphere consists of a bidentate L ligand spanning axial to equatorial sites, two chloride ligands in equatorial sites, and an O ‐bound dimethylformamide ligand in the remaining axial site. The other complex, (II), crystallized as an ethanol solvate. The Zn II atom has a distorted trigonal prismatic coordination geometry, with two bidentate acetate ligands occupying two edges and a bidentate L ligand occupying the third edge of the prism. Complexes (I) and (II) emit in the blue region of the spectrum. The results of density functional theory (DFT) calculations suggest that the luminescence of L results from π*←π transitions and that the luminescence of the complexes results from interligand charge‐transfer transitions. The orientation of the 2‐(pyridin‐2‐yl) substituent with respect to the benzimidazole system was found to have an impact on the calculated HOMO–LUMO gap (HOMO is highest occupied molecular orbital and LUMO is lowest unoccupied molecular orbital).